The capacity of education facilities and the implications for the well-being of the people in Mukim Serendah - Mohd Faizul Muhammad; Mazdi Marzuki; Muhammad Hasbi Abdul Rahman; Kamarul Ismail; Jabil Mapjabil (2018)
The population growth in an area has a strong connection with the capacity of the facilities enjoyed by the population. At present, Mukim Serendah is enjoying rapid population growth. The population growth has impacted some of the provided facilities which are no longer capable to meet the demands of the population. The study was conducted to examine the capacity of education facilities and it implications for the population's wellbeing. This study uses a capacity-based analysis based on the Community Facilities Planning Guidelines issued by the Federal Department of Town and Country Planning Peninsular Malaysia in 2013. The study used secondary data involving population data, number of schools and, number of students. A total of 400 respondents in Mukim Serendah were involved in this study. The study found that there were differences in the capacity of educational facilities in Mukim Serendah. Educational facilities in Mukim Serendah mostly do not meet the targetted standards. The under equipped facilities had affected students, teachers and parents. The results of this study are important to the party responsible for the planning of educational facilities to ensure adequate and better facilities for the residents in the future. Areas that are lacking in the carrying capacity of educational facilities need to be improved by adding the number of schools. Therefore, these educational facilities would meet the needs and improve the wellbeing of the population.